(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The integration of Virtual Reality (VR) technology into the educational process has fundamentally transformed traditional teaching methodologies, especially in experimental sciences such as chemistry. This study examines the development and implementation of a 3D laboratory created using Blender software, allowing chemical reactions to be conducted in a safe environment. Furthermore, it provides opportunities to save resources. The results indicate that VR technology increases students’ engagement, conceptual understanding, and motivation by offering experience‑based learning in a virtual environment.